Exergy analysis of concentrating solar systems for heat and power production. (1st July 2017) - Cocco, Daniele; Petrollese, Mario; Tola, Vittorio
Abstract: The use of concentrating solar technologies for supplying heat and power in industrial processes is investigated in this paper. The thermal energy produced by a solar field is stored in a TES system and subsequently used in a Heat and Power Generation (HPG) section. In particular, three different HPG configurations are analyzed. The electricity is generated in an Organic Rankine Cycle (ORC) unit while the heat is supplied by a heat generator placed in parallel or downstream of the ORC unit or by recovering the ORC waste heat. An exergy analysis is carried out and the plant exergy efficiency is chosen as marker to evaluate the best configuration. Several power-to-heat ratios and the production of saturated steam or hot water are considered. The results show an optimum utilization field for each configuration. The use of a heat generator operating in parallel with the ORC unit is the only suitable solution for supplying high-pressure steam while its placement downstream of the ORC unit is appropriate for low-pressure steam and high power-to-heat ratios. The use of the ORC waste heat is an interesting option for the hot water production but it requires the full use of available heat to avoid significant exergy degradations. Highlights: The use of concentrating solar systems for providing heat and power is analyzed. Three different configurations of the heat and power generation section are compared. An exergy analysis is carried out in order to determine the best option. Several power-to-heat ratios and steam/hot water temperatures are considered. The results recommend the best utilization field of each configuration.